Special exercises according to the use of the high-intensity interval training method and its impact on developing some basic skills of youth basketball players. (Journal of the College of Basic Education, 2023)
The study aims to identify the effect of the special exercises prepared by the researchers to develop some basic skills of the youth basketball players.The study sample amounted to (12) players with ages of (16-18) years, and the research sample was divided into two experimental and control groups equally, with (6) players for each group, and the special exercises prepared by the researchers were applied to the experimental group, by ( 8) weeks and each week (3) training units, with a total of units. Training in the training program, (24) training units, and the time taken In the training unit (40 minutes), and taking into account the correct organization of work and rest time by rationing the intensity of the exercises used in the training units by using the high-intensity interval training method that the researchers used in their study had a positive effect on developing the skills of the experimental group players at the expense of The group is a control group, and after the end of applying the special exercises to the experimental group, post-tests were conducted on the research sample. And then the means were used Appropriate statistics, where the researchers reached several conclusions, including that training using the high-intensity interval training method for the experimental group showed clear superiority in all research tests in relation to the pre- and post-tests. As for the posttests, the experimental group showed a remarkable superiority over the control group in all tests except for the peaceful scoring test.The researchers also recommend the necessity of adopting the use of high-intensity interval training in developing the performance of skills better and with high efficiency throughout the periods of the match, and conducting similar and related research and studies on different age groups and on different events and activities